2007
DOI: 10.1136/gut.2007.120253
|View full text |Cite
|
Sign up to set email alerts
|

The effects of population-based faecal occult blood test screening upon emergency colorectal cancer admissions in Coventry and north Warwickshire

Abstract: Following commencement of the UK Bowel Cancer Screening Pilot, there has been a significant decline in emergency CRC workload with a marked improvement in 30-day mortality and decreased stoma formation, in Coventry and North Warwickshire. It is postulated that the witnessed and notable positive impact over such a short time period is the result of increased detection of asymptomatic malignancies within the screening programme, increased public awareness of the symptoms of CRC, together with a change in attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…Recent figures from the Midlands of England bear these calculations out: in the fifth year of screening, 31 of a total of 200 cancers were identified through the screening programme. 33 Similar figures pertain to breast cancer: 75% of breast cancers are diagnosed outside the mammography programme, for similar reasons. Cervical cancer is an exception, as sensitivity is higher, the age range for screening is wider, and uptake is 72%.…”
Section: Misconception 3: Screening Makes Symptomatic Diagnosis Less mentioning
confidence: 58%
“…Recent figures from the Midlands of England bear these calculations out: in the fifth year of screening, 31 of a total of 200 cancers were identified through the screening programme. 33 Similar figures pertain to breast cancer: 75% of breast cancers are diagnosed outside the mammography programme, for similar reasons. Cervical cancer is an exception, as sensitivity is higher, the age range for screening is wider, and uptake is 72%.…”
Section: Misconception 3: Screening Makes Symptomatic Diagnosis Less mentioning
confidence: 58%
“…7 however, together with the introduction of national bowel cancer-screening program, there was a sharp increase in demand for colorectal services. 5 the national Bowel Cancer awareness Campaign was subsequently designed in an attempt for patients with any suspicious bowel symptoms to seek medical attention. the role of public education was primarily to capture these symptomatic patients who would not otherwise be in the screening group.…”
Section: Discussionmentioning
confidence: 99%
“…in 2011, the government outlined a £750 million plan to improve the outcomes of cancer with the aim of matching the best outcomes in the rest of europe and saving 1700 lives a year. 5 Raising awareness was a key component of this proposal.…”
mentioning
confidence: 99%
“…In a more recent work, a British pilot study indicated a dramatic decrease in emergency admissions for colorectal cancer by virtue of fecal occult blood test screening, 16 although later reports of a local study in Canada 17 and an audit in England 18 showed that rates of emergency admissions for colon cancer remained alarmingly high, despite both areas providing universal health care with a colorectal screening program. A second issue that makes the findings of previous work hard to interpret specifically for colon cancer is the lack of differentiation that all but 2 14,15 of the discussed articles make between colon and rectal disease -an issue shared with many publications on the matter.…”
Section: Commentsmentioning
confidence: 99%